Why Have CO2 Emissions Increased in the Transport Sector in Asia? Underlying Factors and Policy Options - Timilsina, Govinda R.; Shrestha, Ashish (2012)
Rapidly increasing emissions of carbon dioxide from the transport sector, particularly in urban areas, is a major challenge to sustainable development in developing countries. This study analyzes the factors responsible for transport sector CO2 emissions growth in selected developing Asian countries during 1980-2005. The analysis splits the annual emissions growth into components representing economic development; population growth; shifts in transportation modes; and changes in fuel mix, emission coefficients, and transportation energy intensity. The study also reviews existing government policies to limit CO2 emissions growth, particularly various fiscal and regulatory policy instruments. The study finds that of the six factors considered, three - economic development, population growth, and transportation energy intensity - are responsible for driving up transport sector CO2 emissions in Bangladesh, the Philippines, and Vietnam. In contrast, only economic development and population growth are responsible in the case of China, India, Indonesia, Republic of Korea, Malaysia, Pakistan, Sri Lanka, and Thailand. CO2 emissions exhibit a downward trend in Mongolia due to decreasing transportation energy intensity. The study also finds that some existing policy instruments help reduce transport sector CO2 emissions, although they were not necessarily targeted for this purpose when introduced.